On the Relative Growth of Dirichlet Series with Zero Abscissa of Absolute Convergence - Mulyava, Oksana (My University, 2021)
Let F and G be analytic functions given by Dirichlet series with exponents increasing to + ∞ and zero abscissa of absolute convergence.The growth of F with respect to G is studied through the generalized order. Formulas are found for the finding these quantities.
Keywords: dirichlet seriesd; generalized order; relative growth; ряд Діріхле; відносний ріст; узагальнений порядок; кафедра вищої математики імені проф. Можара В. І.